2016
DOI: 10.1186/s12977-016-0296-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of APOL1 polymorphism and IL-1β priming in the entry and persistence of HIV-1 in human podocytes

Abstract: Background Patients of African ancestry with untreated HIV-1 infection and carrying the G1 or G2 kidney disease risk variants (Vs) at the APOL1 gene have a tenfold higher risk of developing HIV-associated nephropathy (HIVAN) compared to those with the non-risk wild type (WT) G0 variant. However, the mechanistic contribution of the APOL1 allelic state to kidney injury in HIV-1 infection remains to be elucidated.ResultsNon-risk WT APOL1 is associated with lower intracellular levels of HIV-1 in conditionally immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…In renal cells, one study reported HIV-1 infections of podocytes isolated from individuals with a highrisk and a low-risk genotype were not different with regard to supporting HIV infection (33). However, in another study, APOL1 overexpression in a commonly used podocyte cell line found HIV-1 uptake and persistence were greater with the risk variants compared with G0, suggesting anti-HIV functions observed in monocytes and T cells may also occur in podocytes and the risk variants may have a reduced ability to suppress infection (42).…”
Section: Loss-of-functionmentioning
confidence: 89%
“…In renal cells, one study reported HIV-1 infections of podocytes isolated from individuals with a highrisk and a low-risk genotype were not different with regard to supporting HIV infection (33). However, in another study, APOL1 overexpression in a commonly used podocyte cell line found HIV-1 uptake and persistence were greater with the risk variants compared with G0, suggesting anti-HIV functions observed in monocytes and T cells may also occur in podocytes and the risk variants may have a reduced ability to suppress infection (42).…”
Section: Loss-of-functionmentioning
confidence: 89%
“…However, in the absence of such adverse milieus, it is considered that APOL1 expression may be dispensable to kidney health (19). Since LPS, TNF-␣, human immunodeficiency virus, and IFN-␥ have been reported to enhance expression of APOL1 in podocytes (23,24,27), these agents could be used to prevent downregulation of APOL1 in high-glucose milieu. However, these agents are phlogogenic de novo and would not be suitable in chronic kidney disease-carrying pre-existing inflammatory milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of a stable cell lines expressing APOL1G0 and vector. A stable cell line expressing APOL1G0 was generated by retroviral infection as described previously (27). Briefly, the open reading frame of APOL1G0 was cloned into the retroviral vector pBABE carrying resistance to puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, Mikulak and colleagues studied the effect of APOL1 transfection on HIV infection of cultured podocytes (Mikulak et al 2016). The APOL1 G0 variant reduced viral accumulation, while APOL1 risk variants increased viral accumulation.…”
Section: Apol1 and The Molecular And Cellular Mechanisms Of Hivanmentioning
confidence: 99%